Biodegradation Capability Analysis of Petroleum Hydrocarbon by Marine Bacteria Isolate From Territorial Water Column of Paotere Port Makassar as In Vitro - Asrianty Mas'ud (Universitas Hasanuddin, 2018)
The research about the biodegradation capability analysis of petroleum hydrocarbon by marine bacteria isolate from territorial water column of Paotere port Makassar as in vitro was conducted. The aim of this research was to know the biodegradation capability of petroleum hydrocarbon quantitatively by marine bacteria isolate from water column in Paotere port, Makassar. This research consist of two phases of working, those are characteristic of hydrocarbon degraded bacteria and quantitative process of hydrocarbon biodegradable from degraded bacteria. The result shows there are three different isolates ; isolate A in bacilli shape (Gram negative), isolate B in coccus shape (Gram negative), and isolate C in coccus shape (Gram positive) and the capability to degrading hydrocarbon from the highest respectively are isolate B (83,91%), isolate A (80,53%), and isolate C (72,86%).